Epidemiology and Public Health Implications of Mycobacterium tuberculosis complex and Non-tuberculous mycobacteria in Cattle and Humans in Oyo State, Nigeria (2015)
The risks of humans contracting bovine tuberculosis (BTB) and other mycobacterial infections abound in Nigeria. This could be attributed to the close association between farmers and cattle, unhealthy meat processing practices by butchers, consumption of unpasteurized milk and milk products, and poor knowledge of the disease. The circulating Mycobacterium tuberculosis complex and non-tuberculous mycobacteria in livestock workers and animals are largely unknown. Confirming the sources of exposure in humans will help to guide the direction of prevention and control of the diseases. This study aimed at determining the prevalence of tuberculosis and characterising the mycobacterial species in cattle, livestock workers as well as identifies risk factors associated with the infection in Oyo State. A cross-sectional study was conducted among cattle and livestock workers in the five local government areas (LGA) in Ibadan metropolis, Iwajowa, Ibarapa North, Kajola, Oyo West and Akinyele LGAs. These sites are characterised by cattle population and dairy activities.Fresh milk from 269 pastoral cattle; 295 cheese “wara”; 150 fermented milk “nunu”; 124 nasal secretions and 124 faecal samples of slaughtered cattle; with 93 sputum samples from livestock workers collected by multistage sampling were analysed for the presence of Mycobacterium species using conventional culture method, multiplex polymerase chain reaction (PCR) and restriction enzyme analysis-hsp65. Furthermore, a survey to investigate the knowledge, attitude and practices with regards to BTB using pre-tested structured questionnaires was conducted on 124 livestock workers (Herdsmen = 42, Cattle traders = 42 and Butchers = 40) via multistage sampling technique. Data were analysed using chi square and odds ratio at P= 0.05 level of significance. Mycobacterium species were isolated from 8.3%, 0.3%, 5.7%, and 1.6% fresh milk samples, cheese, nasal swabs and faecal samples respectively then 2.2% from sputum. Multiplex PCR revealed five strains of M. africanum (fresh milk = 2; cheese = 1 and sputum = 2) and a high prevalence (86.8%) of non-tuberculous mycobacteria (NTM): 24 from fresh milk, seven from nasal secretions and two from faeces. Diverse strains of NTM were also obtained (M. gordonae =16; M. fortuitum =12; M. senegalense =8; M. avium =1). Significant association was observed between isolation of mycobacteria and types of sample; with fresh unpasteurised milk being 26 times more likely to have mycobacteria isolated (OR: 26.2; 95% CI 3.5 – 195.7). Livestock workers were knowledgeable about BTB transmission, with their occupation significantly affecting their knowledge. However, most livestock workers (70%) consume unpasteurised milk, 30% of butchers consume raw meat, and all agreed to consumption, selling or sharing of suspected infected animal products to the public. The isolation of M. africanum and predominance of non-tuberculous mycobacteria highlight their significance in the epidemiology of tuberculosis. Also, the isolation of M. senegalense an emerging infectious agent in fresh milk and nasal secretion of cattle has been established. Public health enlightenment of livestock workers on risk of consuming unpasteurized milk or milk products, raw or undercooked meat and meat products and precautions when handling infected animals is recommended.